Discurso, escritura e historia en l’idéologie de Destutt de Tracy - Nocera, Pablo (Nómadas. Critical Journal of Social and Juridical Science, 2009)
Considering the philosophical and political dimension of the ideologues’ project in France during the Great Revolution, the paper analyses the fundamentals of Destutt de Tracy’s work, Éléments d’Idéologie, with two aims. Firstly, to characterize the concept of ideology in epistemological terms, considering the knowledge integration that this science des idées, according to the author, would allow. Secondly, to notice the importance of the reflection about language as the material expression of intellectual processes whose source is the experience. Regarding this precedent, the paper focuses the analysis in the second volume of the mentioned text (Grammaire) with two objectives: a) to notice that without an analytical of discourse, ideology can’t develop as a science, in other words, to produce a good reasoning it is necessary to know how language logically works. b) to emphasize that the author’s analysis about writing practice is more than a gnoseological or a communicative issue, but a political problem whose study allows the construction of a democratic and a educational access to knowledge (public instruction) as well as the constitution of national history with the view to progress.